(untitled) (Revista Contexto & Educação, 2022)
Currently, the level of recognition and perception that young people have about responsible health issues is low. Therefore, in adolescence, health-related aspects are not considered essential. This conception in the young population leads, from an early age, to exposure to health risks and problems related to the consumption and ingestion of various substances. Among this diversity of substances, there are drugs (depressants, stimulants and hallucinogens) and foods that are ingested without taking into account the consequences of their consumption and sometimes cause damage to the body. Thus, Health Education is an emerging theme in education and its connection with the science classroom significantly contributes to the development of critical thinking and healthy attitudes. Thus, a documental study is presented, whose objective is to recognize the theoretical constructions around the dimension of addictions and scientific education. For this, 23 academic references were reviewed, including undergraduate and graduate theses, compiled in indexed journals, databases and bibliographic repositories. Systematization was carried out with the Educational Analytical Summary - RAE and, based on that, a review matrix was built. Among the most relevant findings, the grouping of the revised material into three discursive categories stands out: Drugs in the Science Classroom Uses of Psychoactive Substances and Health Education - Drugs. Thus, methodological guidelines aimed at preventing drug use are recognized, that is, positions of a biological and clinical nature. On the contrary, records that formally include the subject in the classroom are few, due to emotions such as apathy and disinterest in the faculty and the tendency to think of addictions as a matter of psychology.